Research on the Precision Marketing and Optimization of Pinduoduo in the Context of Big Data - Tang Jiangting (Pacific International Journal, 2022)
Precision marketing is widely used in mobile applications at present, and big data provides a technical foundation for precision marketing. Precision marketing refers to the use of big data technology to push marketing content to target users through various new media to maximize marketing effects. The implementation of precision marketing through big data has the characteristics of accuracy, large amount of data and target customer-oriented. As an emerging Chinese e-commerce enterprise, Pinduoduo positioned itself as the pioneer of new e-commerce. It is the third-party social e-commerce application focusing on Customer-to-Manufacturer group shopping, that is, with the original social group shopping as the core mode. On the basis of previous research, this paper analyzes the advantages of precision marketing for Pinduoduo under the background of big data, including reducing marketing costs, improving marketing efficiency, reducing the cost of meeting target customers and flexibly adjusting marketing strategies. Pinduoduo still faces some problems despite its rapid development, including the fatigue of target customers due to a large amount of information push, lack of professionals proficient in big data analysis, the possibility of data security risks and the imperfect legal and regulatory system related to big data and precision marketing. Finally, this paper puts forward some suggestions to optimize the precision marketing of Pinduoduo under the background of big data from four aspects: respecting the choice of target customers, introducing professionals related to big data analysis and mining, training on data security knowledge, and further improving laws and regulations related to big data and precision marketing.